2017
DOI: 10.3823/2448
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with uremic pruritus

Abstract: Background: The etiopathogenesis of uremic pruritus (UP) is multifactorial aspect, and it is thus necessary to elucidate its associated factors to develop efficient therapeutics approaches. This study aimed to verify the prevalence of UP and its associated factors. Methods and Findings:Prospective and cross-sectional study with patients undergoing hemodialysis at a university public hospital. The data were obtained between April 2014 and April 2015. The statistical analysis was carried out using multivariate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
4
7
0
Order By: Relevance
“…In a study by Ozen et al [6] regarding the factors that influence pruritus, it was found that patients with high levels of leukocytes and dry skin types experienced severe pruritus. Oliviera et al [7] found that pruritus has a high prevalence in high creatinine levels and low hemoglobin levels. Oliviera et al [7] also mention that high pruritus intensity can be affected by dyslipidemia, obesity, and high C-Reactive Protein (CRP) levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Ozen et al [6] regarding the factors that influence pruritus, it was found that patients with high levels of leukocytes and dry skin types experienced severe pruritus. Oliviera et al [7] found that pruritus has a high prevalence in high creatinine levels and low hemoglobin levels. Oliviera et al [7] also mention that high pruritus intensity can be affected by dyslipidemia, obesity, and high C-Reactive Protein (CRP) levels.…”
Section: Introductionmentioning
confidence: 99%
“…Oliviera et al [7] found that pruritus has a high prevalence in high creatinine levels and low hemoglobin levels. Oliviera et al [7] also mention that high pruritus intensity can be affected by dyslipidemia, obesity, and high C-Reactive Protein (CRP) levels. In contrast, the low intensity of pruritus is associated with the use of a high flow dialyzer.…”
Section: Introductionmentioning
confidence: 99%
“…Doing so can assist in the execution of strategies such as dialysis adequacy and metabolic stabilization, which can be adopted along with drug treatment. [10]…”
Section: Introductionmentioning
confidence: 99%
“…Many factors are also believed to be the cause of pruritus. Research conducted by Gobo-Oliveira et al (4) showed a higher pruritus intensity occurred in patients with high creatinine, low hemoglobin, dyslipidemia, high CRP levels, and black race. In contrast, lower pruritus intensity was associated with high dialyzer use.…”
Section: Introductionmentioning
confidence: 96%